Dietary cation anion difference and acidified coproducts: effects on peripartum dairy cows - Rezac, Darrel James (Kansas State University, 2010)
The transition from gestation to lactation requires numerous physiological and metabolic adaptations in order for the body to maintain relative homeostasis. For the modern dairy cow, the difficulty to meet these challenges is increased many-fold due to the large demand for energy and metabolites placed on the body by the high producing mammary gland. Milk fever or periparturient hypocalcemia can be defined as a failure of the calcium homeostatic mechanisms to maintain serum calcium around the time of calving. Though clinical cases may only arise in ≈ 5% of transition cows, subclinical rates are much higher. Animals suffering from even subclinical milk fever are much more susceptible to numerous other transition disorders. Preventing milk fever by formulation of the prepartum ration may be accomplished by decreasing the dietary cation anion difference (DCAD) which can be defined as the balance between positively and negatively charged ions in the diet. An experiment was designed to test 2 diets containing t products designed to deliver supplementary anions to the diet versus a control ration with no added anions. Total serum calcium and incidence of postpartum health disorders were not affected by prepartum dietary treatment. Though DCAD was drastically different between the control ration and the 2 anionic diets, the concentration of the strong cation potassium was low across all treatments which presumably prevented hypocalcemia with the onset of lactation. Though our diets contained low concentrations of potassium, many diets used by dairymen contain forages that are high in potassium and thus might benefit from the addition of anions. An experiment of an unrelated nature was conducted to observe the effects of 2 diets containing wet corn gluten feed (46 or 56% of DM) as the primary energy substrate and tallgrass prairie hay (14 or 20% of DM) as the sole source of physically effective fiber versus a control ration containing alfalfa and corn silage. The 20% tallgrass prairie hay diet resulted in milk components and efficiencies similar to those of the control ration, but production and income over feed cost did not match that of the control ration in this situation.
Keywords: Dietary Cation Anion Difference; Wet Corn Gluten Feed; Agriculture, Animal Culture and Nutrition (0475)